Enhancing Arabic Speaking Skills in Indonesian Madrasahs - Anggraini, Niatri; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2024)
This research investigates the implementation of the Drilling Arabic Program (DAP) in enhancing speaking skills at the Junwangi Krian Siadoarjo Bilingual Madrasah Aliyah. Using qualitative methods, educators and students were surveyed to identify supporting and inhibiting factors and propose solutions. Findings reveal that while DAP is divided into planning, implementation, and evaluation stages, supporting factors include teacher competence and student enthusiasm, while inhibiting factors include teachers' lack of approach and inadequate infrastructure. Solutions include optimizing teacher development groups, improving time management, encouraging Fus-ha Arabic usage, and enhancing infrastructure. These results provide insights for improving Arabic language education in madrasahs and preserving Islamic linguistic heritage. Highlight: 1. DAP Implementation Stages: Planning, executing, and evaluating Arabic speaking skill enhancement.2. Key Supporting Factors: Teacher competence, student enthusiasm, and available infrastructure.3. Addressing Challenges: Teacher approach, understanding, and infrastructure; solutions proposed. Keyword: Drilling Arabic Program, Madrasah Aliyah, Speaking Skills, Qualitative Research, Language Education